Characteristic and overlapping features of migraine and tension-type headache - TÜRKDOĞAN, DİLŞAD (WILEY, 2006)
Objective.-This epidemiological survey was conducted to investigate comprehensive characteristic and overlapping features of migraine and tension-type headache (TTH) disorders classified based on International Classification of Headache Disorders-II. Methods.-The stratified cohort of this study was composed of 2504 schoolchildren aged 10 to 17 years. A 38-item questionnaire inquiring all characteristic features of primary headache syndromes mandatory for classification was applied to selected 483 children with recurrent headache in the last 6 months. Results.-Migraine was diagnosed in 227 (47.0%) of 483 children and TTH in 154 (31.9%). Out of 125 children with definite migraine, 73 (58.4%) reported tension-type symptoms and 94 (68.1%) of 138 children with definite TTH reported migraine-type symptoms. Pressing pain (21%) and lack of aggravation of pain by physical activity (34%) were the major tension-type features in patients with migraine. Throbbing quality (43%) and aggravation by physical activity (30%) determined the main migraine-type features in patients with TTH. Conclusion.-The frequent co-occurrence of migraine and TTH symptoms suggests the presence of a common pathogenesis.
Keywords: pediatric headache; migraine; tension-type headache; overlapping symptoms; CLASSIFICATION CRITERIA; DIAGNOSTIC-CRITERIA; PEDIATRIC MIGRAINE; CHILDHOOD; CHILDREN; ADOLESCENTS; POPULATION; AGE